Associations between biomarkers of matrix metabolism and inflammation with pain and fatigue in participants suspected of early hip and or knee osteoarthritis: data from the CHECK study. Issue 12 (December 2022) - van Berkel, A.C.; van Spil, W.E.; Schiphof, D.; Runhaar, J.; van Ochten, J.M.; Bindels, P.J.E.; Bierma-Zeinstra, S.M.A.
Summary: Objectives: To assess the associations of biomarkers in serum [highsensitivity C-reactive protein (hs-CRP), serum cartilage oligomeric protein (sCOMP), serum propeptide of type I procollagen (sPINP) and serum osteocalcin (sOC)] and urine [urinary type II collagen telopeptide (uCTX-2)] with the extent and progression of nocturnal pain, pain while walking, and fatigue in participants with hip and/or knee pain suspected to be early stage osteoarthritis (OA). Methods: hs-CRP, uCTX-2, sCOMP, sPINP and sOC were measured at baseline in 1, 002 participants of the Cohort Hip and Cohort Knee (CHECK). Nocturnal pain, pain while walking and fatigue were assessed by self-reported questionnaires at baseline and 2-year follow-up. Associations between these biomarkers and symptoms were examined using logistic and linear regression analyses. Results: hs-CRP was significantly associated with mild nocturnal pain (OR 1.18 95% CI 1.01–1.37), with mild and moderate pain while walking (OR 1.17 95% CI 1.01–1.35 and OR 1.56 95% CI 1.29–1.90, respectively) and with progression of nocturnal pain (OR 1.25 95% CI 1.07–1.46). uCTX-2 was associated with mild nocturnal pain (OR 1.40 95% CI 1.05–1.85) and with mild and severe-extreme pain while walking (OR 1.35 95% CI 1.04–1.75 and OR 2.55 95% CI 1.03–6.34, respectively). sPINP was associated with severe-extreme nocturnal pain (OR 0.45 95% CI 0.25–0.82). No significant associations were found for sCOMP and sOC, nor for any of the biomarkers and fatigue. Conclusion: This study of biomarkers in a large cohort of participants with hip and/or knee pain suspected to reflect early stage hip and/or knee OA suggests that inflammation and cartilage matrix degeneration play a role in pain, but not in fatigue.